Analisis Kinerja Aparat Dinas Pemuda, Olahraga, Budaya dan Pariwisata dalam Mengembangkan Bakat Siswa SMP pada Bidang Olahraga di Kecamatan Baranti - Darmawati Darmawati (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2019)
Abstract The purpose of this research was to determine the Department of Youth, Sports, Cultural, and Tourism officials’ performance in developing junior high school students’ talent in the field of sports in Baranti District, along with all affecting factors. This research used quantitative method which calculate qualitative data into numerical data. Data collection methods used were observation, interviews, questionnaires, and literature study. The population in this research are government officials – the Department of Youth, Sports, Cultural, and Tourism officials, the sports teacher, all junior high school students in four public schools located in Baranti District who had talent in sports. The samples were determined by the level of the standard error table. Total population were 129 people in this study, then with an error level of 1%, the samples taken were 109 people. The results of this study indicate that the performance appraisal apparatus Department of Youth, Sports, Culture and Tourism in developing talent in the field of sports junior high school students in Baranti District are in the category of quite well with the value of 2,998. These results were obtained from all factors which summaried the accuracy with a score of 3,14, professionalism scored 2,30, overall facilities scored 2,46, and the other two factors were rules clearness and discipline scored 3,27 and 3, 82 respectively.